Mimicking human riboflavin responsive neuromuscular disorders by silencing flad‐1 gene in C. elegans: Alteration of vitamin transport and cholinergic transmission. Issue 7 (24th September 2021) - Leone, Piero; Tolomeo, Maria; Piancone, Elisabetta; Puzzovio, Pier Giorgio; De Giorgi, Carla; Indiveri, Cesare; Di Schiavi, Elia; Barile, Maria
Abstract: Riboflavin (Rf), or vitamin B2, is the precursor of FMN and FAD, redox cofactors of several dehydrogenases involved in energy metabolism, redox balance and other cell regulatory processes. FAD synthase, coded by FLAD1 gene in humans, is the last enzyme in the pathway converting Rf into FAD. Mutations in FLAD1 gene are responsible for neuromuscular disorders, in some cases treatable with Rf. In order to mimic these disorders, the Caenorhabditis elegans ( C. elegans ) gene orthologue of FLAD1 ( flad‐1 ) was silenced in a model strain hypersensitive to RNA interference in nervous system. Silencing flad‐1 resulted in a significant decrease in total flavin content, paralleled by a decrease in the level of the FAD‐dependent ETFDH protein and by a secondary transcriptional down‐regulation of the Rf transporter 1 ( rft‐ 1) possibly responsible for the total flavin content decrease. Conversely an increased ETFDH mRNA content was found. These biochemical changes were accompanied by significant phenotypical changes, including impairments of fertility and locomotion due to altered cholinergic transmission, as indicated by the increased sensitivity to aldicarb. A proposal is made that neuronal acetylcholine production/release is affected by alteration of Rf homeostasis. Rf supplementation restored flavin content, increased rft‐1 transcript levels and eliminated locomotion defects. In this aspect, C. elegans could provide a low‐cost animal model to elucidate the molecular rationale for Rf therapy in human Rf responsive neuromuscular disorders and to screen other molecules with therapeutic potential.